Regulatory Role of Fc Receptor in mIgM+ B Lymphocyte Phagocytosis in Flounder (Paralichthys olivaceus) - Hao, Yanbo; Tang, Xiaoqian; Xing, Jing; Sheng, Xiuzhen; Chi, Heng; Zhan, Wenbin (Frontiers in Immunology, 2021)
Fc receptor (FcR) is an important opsonin receptor on the surface of immune cells, playing an important role in antibody-dependent cell-mediated immunity. Our previous work found that the FcR of flounder showed a marked expression response in phagocytizing IgM+ B cells, which suggested FcR might participate in regulating Ig-opsonized phagocytosis. In this paper, in order to elucidate the potential role of FcR in mediating phagocytosis of IgM+ B cells, flounder anti-E. tarda serum was prepared and complement-inactivated for the use of E. tarda opsonization, and the sera of healthy flounder was used as control. Flow cytometric analysis showed that the phagocytosis rates of antiserum-opsonized E. tarda in peripheral blood mIgM+ B lymphocytes were significantly higher than the control group, and higher phagocytosis rates of mIgM+ B lymphocyte could be detected with an increasing incubation time ranging from 1 to 5 h. The phagocytosis rates of antiserum-opsonized E. tarda by mIgM+ B lymphocyte for an incubation time of 1, 3 or 5 h were 51.1%, 63.0% and 77.5% respectively, which were significantly higher than the phagocytosis rates in control groups with 40.2%, 50.9% and 63.8%, respectively. While the Fc fragment of IgM on the surface of opsonized E. tarda was blocked by rabbit anti-flounder IgM polyclonal antibodies, phagocytosis rates of mIgM+ B lymphocyte decreased significantly compared with unblocked group. Moreover, the proportion of mIgM+ B lymphocytes with higher intracellular reactive oxygen species (ROS) levels raised to 32.1% from the control level of 23.0% after phagocytosis of antiserum-opsonized E. tarda. FcγRII and Syk were found to be significantly up-regulated, while FcγRIII was significantly down-regulated in the mIgM+ B lymphocytes post phagocytosis. Furthermore, When FcγRII of mIgM+ B lymphocytes was blocked by the prepared antibodies, their phagocytosis rate of antiserum-opsonized E. tarda was 39.0%, which was significantly lower than the unblocked group of 54.0%. These results demonstrate that FcR plays a critical role in mediating phagocytosis and bactericidal activity of mIgM+ B lymphocytes, which would facilitate an improved understanding of the regulatory roles of FcR in phagocytosis of teleost B lymphocytes.